Interactive Web-based Portals to Improve Patient Navigation and Connect Patients with Primary Care and Specialty Services in Underserved Communities. - Highfield, Linda; Ottenweller, Cecelia; Pfanz, Andre; Hanks, Jeanne (Perspectives in Health Information Management)
This article presents a case study in the redesign, development, and implementation of a web-based healthcare clinic search tool for virtual patient navigation in underserved populations in Texas. It describes the workflow, assessment of system requirements, and design and implementation of two online portals: Project Safety Net and the Breast Health Portal. The primary focus of the study was to demonstrate the use of health information technology for the purpose of bridging the gap between underserved populations and access to healthcare. A combination of interviews and focus groups was used to guide the development process. Interviewees were asked a series of questions about usage, usability, and desired features of the new system. The redeveloped system offers a multitier architecture consisting of data, business, and presentation layers. The technology used in the new portals include Microsoft .NET Framework 3.5, Microsoft SQL Server 2008, Google Maps JavaScript API v3, jQuery, Telerik RadControls (ASP.NET AJAX), and HTML. The redesigned portals have 548 registered clinics, and they have averaged 355 visits per month since their launch in late 2011, with the average user visiting five pages per visit. Usage has remained relatively constant over time, with an average of 142 new users (40 percent) each month. This study demonstrates the successful application of health information technology to improve access to healthcare and the successful adoption of the technology by targeted end users. The portals described in this study could be replicated by health information specialists in other areas of the United States to address disparities in healthcare access.